1985
DOI: 10.1007/bf00214565
|View full text |Cite
|
Sign up to set email alerts
|

Localization of substance P-like, leucine-enkephalin-like, methionine-enkephalin-like, and FMRFamide-like immunoreactivity in the eyestalk of the fiddler crab, Uca pugilator

Abstract: The occurrence and distribution of substance P (SP)-like, methionine-(Met)- and leucine-(Leu)-enkephalin-like, and FMRFamide-like immunoreactivities were determined in the neuroendocrine complex of the eyestalk of the fiddler crab, Uca pugilator, by immunocytochemistry. SP-like immunoreactivity was found in the optic peduncle, sinus gland, medulla externa, medulla interna, lamina ganglionaris, and retinular cells. Met-enkephalin-like and Leu-enkephalin-like immunoreactivity was observed in most of the retinula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…While Carcinus maenas is the only crustacean from which enkephalins have been fully characterized, biochemical/ immunohistochemical data suggest they are broadly conserved in the taxon [129][130][131][132][133][134][135][136]; these data also suggest that the enkephalins function both as locally released autocrines/ paracrines and circulating hormones in crustaceans.…”
Section: Enkephalinmentioning
confidence: 91%
“…While Carcinus maenas is the only crustacean from which enkephalins have been fully characterized, biochemical/ immunohistochemical data suggest they are broadly conserved in the taxon [129][130][131][132][133][134][135][136]; these data also suggest that the enkephalins function both as locally released autocrines/ paracrines and circulating hormones in crustaceans.…”
Section: Enkephalinmentioning
confidence: 91%
“…The appearance of FLI in several regions within the eyestalks of the fiddler crab Uca pugilator suggested that FLPs might function as neurotransmitters or as neurohormones (Fingerman et al, 1985). Subsequently, injection of FMRFamide and other neuropeptides into intact fiddler crabs was shown to produce dark adaptation by stimulating the release of distal retinal pigment dark-adapting hormone from the eyestalk neuroendocrine complex (Kulkami and Fingerman, 1987).…”
Section: Identified Crustacean Flpsmentioning
confidence: 97%
“…Fingerman et al [45] reported the presence of two types of peptides methionine-enkephalin and leucineenkephalin from neuroendocrine complex of eyestalk of fiddler crab U. pugilator. Later, based on experimental evidences proved the role of opioids like methionine-enkephalin as a neurotrasmitter that regulates the secretion of hyperglycemic hormone in fiddler crab U. pugilator, movement of red pigment molecules that regulates chromatophores and on ovarian maturation in U. pugilator.…”
Section: Role Of Opioids On Moltingmentioning
confidence: 99%